2021
DOI: 10.1177/1747954121991817
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ impact on youth athletes’ intentions to continue sport participation: The mediational influence of the coach–athlete relationship

Abstract: About 70% of youth athletes drop out of sport by age 13. Self-determination theory has been utilised to investigate athletes’ motivations for behaviours including sport persistence (i.e. continuation) and suggests that the coach can be an influence on such motivations. Basic need fulfillment via interpersonal coaching behaviours, the coach-athlete relationship (CAR), and intentions to continue sport participation have been examined independently and in various combinations and directions, but these variables h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Participants indicated on several occasions that they had to get used to a new coaches’ demands, style, and training routines, which often led to a dropout from sports. This connects to previous research that has shown that the quality of coach-athlete relationships is crucial for a continued participation in sport activities [e.g., 83 , 84 ].…”
Section: Resultssupporting
confidence: 84%
“…Participants indicated on several occasions that they had to get used to a new coaches’ demands, style, and training routines, which often led to a dropout from sports. This connects to previous research that has shown that the quality of coach-athlete relationships is crucial for a continued participation in sport activities [e.g., 83 , 84 ].…”
Section: Resultssupporting
confidence: 84%
“…The fact that competencesupporting behavior of coaches can positively affect the qua lity of communication between coaches and athletes and the decision of young people to continue sports activities, is also confirmed by Wekesser et al (2021) results. The research results of the authors Shen et al (2010) reveal that the tutor's support in the context of autonomy and competence relationships is important for reducing the amotivation of athletes.…”
Section: Discussionsupporting
confidence: 61%
“…Interpersonal behavior in the context of sports activities has been extensively studied (Edmunds et al, 2008;Ng et al, 2013;Rocchi, & Pelletier, 2018;Teixeira et al, 2018;Rodri gues et al, 2021). The perception of supportive and thwarting interpersonal behavior style in sports has been investigated (Mladenović et al, 2015;Wekesser et al, 2021;McHenry et al, 2021;McHenry et al, 2022); educator support has been studied in terms of amo tivation (Shen et al, 2010;Vansteenkiste & Ryan, 2013); students (students in physical education) are perceived by the teachers' motivational style, based on the satisfaction of human innate basic psychological needs (Haerens et al, 2018;Burgueño et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the instructor/coach has no significant effect on regular participation, athletic potential, focus and discipline, resiliency and humility, harmony and unity, and the health status of student-athletes. Results of the analysis opposed previously conducted studies on the positive effect of instructor/coach on the frequency of participation of student-athletes (Manzoor, 2018;Wekesser et al, 2021), the potential of athletes through feedbacks (Sumarna et al, 2017;U zu m, 2018), focus and discipline (Goffena & Horn, 2021), resiliency and humility (Balcombe & De Leo, 2021;Brandt, 2018;Lu et al, 2016), harmony and unity (Freire et al, 2022;Vahdani et al, 2012), and their health status (Bissett et al, 2020;Powers et al, 2020;Simons & Bird, 2022).…”
Section: Resultsmentioning
confidence: 59%